Temperature and material behaviour effects on dynamic responses of asphalt concrete trackbed. Issue 1 (2nd January 2020) - Yusupov, Bekhzad; Qiu, Yanjun; Ding, Haibo; Rahman, Ali
ABSTRACT: Developing a simulation model for railway subgrades is an important initial step towards a reliable design for a dense-graded asphalt concrete trackbed. This paper presents a comparative simulation study of the dynamic responses in terms of tensile strains and vertical displacements of the elastic and viscoelastic subgrade surface materials affected by different thermal loadings using the finite element method. The simulations for all conditions were performed with a train speed of 350 km/h. The relationship between different thermal loads and dynamic responses of the railway track materials in terms of tensile strain and vertical displacement was defined. This relationship indicated that the resultant tensile strains and vertical displacements for the viscoelastic material were greater than those of the elastic material at the same thermal load.